1996
DOI: 10.1207/s15327655jchn1302_6
|View full text |Cite
|
Sign up to set email alerts
|

Health Practices Among Russian and Ukrainian Immigrants

Abstract: Since 1990, due to political and legislative changes, immigration from the former Soviet Union to the United States has increased significantly. Population reports from 1988 indicate that there were approximately 406,000 Soviet immigrants in the United States at that time. This number is expected to increase due to the Immigration Reform Act of 1990, which raised the Soviet refugee ceiling to 50,000 per year. Currently, very little is known about the health status and health practices of this population, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 9 publications
0
38
0
1
Order By: Relevance
“…Das auffälligste Ergebnis dieser Studie bezüglich der Gesundheitsversorgung ist die geringe Teilnahme von Aussiedlern an Krebsvorsorgeuntersuchungen. Ähnliche Ergebnisse sowie mögliche Erklärungen, wie kulturelle Hintergründe, Sprachprobleme und Mangel an Information, wurden in einer anderen Studie aufgezeigt (Duncan & Simmons 1996). Generell gilt, je kür-zer die Aufenthaltsdauer in Deutschland, desto geringer ist die Teilnahme an Krebsvorsorgeuntersuchungen.…”
Section: Gesundheitsversorgungunclassified
“…Das auffälligste Ergebnis dieser Studie bezüglich der Gesundheitsversorgung ist die geringe Teilnahme von Aussiedlern an Krebsvorsorgeuntersuchungen. Ähnliche Ergebnisse sowie mögliche Erklärungen, wie kulturelle Hintergründe, Sprachprobleme und Mangel an Information, wurden in einer anderen Studie aufgezeigt (Duncan & Simmons 1996). Generell gilt, je kür-zer die Aufenthaltsdauer in Deutschland, desto geringer ist die Teilnahme an Krebsvorsorgeuntersuchungen.…”
Section: Gesundheitsversorgungunclassified
“…These aspects include lifestyles such as heavy smoking, high alcohol intake, diets based mostly on bread and processed meats, as well as hesitation in seeking health care, which is possibly related to distrust that they developed with health care systems in the Soviet era. 22,[29][30][31][32] For example, in 2 different qualitative studies, Russian immigrants defined health as an absence of disease or pain and reported seeking medical help only when they were already sick and only after home remedies failed to help. 30,32 Even though there was an understanding that behavior affects health, older Russian immigrants were not able to give clear answers on how to exercise or eat healthfully.…”
Section: Introductionmentioning
confidence: 99%
“…Research on FSU natives in Europe and Israel indicates they experience health disadvantages relative to natives of those countries [24][25][26]. FSU immigrants in the U.S. have received little attention in the health literature, but the few existing studies have found high rates of obesity, hypertension, and diabetes among FSU immigrants [27][28][29]. These health problems may be related to cultural practices, such as an attachment to traditional Slavic foods [30].…”
Section: Conceptual Frameworkmentioning
confidence: 99%